Reinventing religion : beyond belief and scepticism - Moore, Peter (Reaktion Books, Limited, 2020)
"Many of us, proponents and critics alike, commonly make assumptions about religion. We may presume that religion is mainly about having beliefs or being good, or that it is concerned with spiritual rather than material issues, or that religious ideas and practices are meant to be somehow timeless. Such views, Peter Moore argues, work only to obscure the truth that religion is essentially humanity's quest to become fully human. This enlightening exposition questions our very understanding of faith and contends that religions should remain open to reinventing themselves, both practically and intellectually, rediscovering neglected traditions and finding new ways forward. Written with subtlety and passion, this book gets to the heart of ongoing debates about the validity and purpose of religion"--